2019
DOI: 10.1007/978-3-030-11009-3_43
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Networks for Object Category and 3D Pose Estimation from 2D Images

Abstract: Current CNN-based algorithms for recovering the 3D pose of an object in an image assume knowledge about both the object category and its 2D localization in the image. In this paper, we relax one of these constraints and propose to solve the task of joint object category and 3D pose estimation from an image assuming known 2D localization. We design a new architecture for this task composed of a feature network that is shared between subtasks, an object categorization network built on top of the feature network,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…We use θ = π 6 , which is a default setting in the literature. A popular approach for solving viewpoint estimation is to cast the problem as bin classification by discretiziing the space of (a, e, θ) [37,21,30,19]. Since network architecture governs the performance of a neural network, we re-train the baseline models [37] with more modern network architectures [6].…”
Section: Viewpoint Estimationmentioning
confidence: 99%
“…We use θ = π 6 , which is a default setting in the literature. A popular approach for solving viewpoint estimation is to cast the problem as bin classification by discretiziing the space of (a, e, θ) [37,21,30,19]. Since network architecture governs the performance of a neural network, we re-train the baseline models [37] with more modern network architectures [6].…”
Section: Viewpoint Estimationmentioning
confidence: 99%
“…They call this network R-CNN. Later, other researchers modified and used this network to recognise and detect the objects for autonomous driving and object localisation [ 14 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, almost all of these networks rely heavily on the textural information of the objects.…”
Section: Related Workmentioning
confidence: 99%
“…Other authors proposed new architecture with a shared feature network, i.e. first a classifier network operated on extracted features, and finally a respective pose regression networks were engaged separately for each of resulting 12 classes [18]. The feature extractor was based on ResNet-50 stages 1 to 4, then 3 additional FC layers were added and trained for each class pose estimation.…”
Section: Related Workmentioning
confidence: 99%
“…Summarizing, we have observed that convolutional networks are able to extract meaningful features from the image, and were also proven to perform accurate regression. It was stated that the same features are useful both for the classification and for localization [10,18], and networks such as VGG performed exceptionally good in both classification and localization competitions [6]. Therefore we aimed at determining and evaluating a DNN architecture performing both tasks at the same time.…”
Section: Related Workmentioning
confidence: 99%